Teeling Whiskey Company : a tradition of family entrepreneurship and whiskey distilling - O'Gorman, Colm; Brophy, Martina; Clinton, Eric (London : SAGE Publications Ltd, 2017)
This case study explores the origins of a new high-growth family start-up competing in a traditional industry. Teeling Whiskey Company Ltd (TWC) is the brainchild of entrepreneur Jack Teeling. This new venture stems from another high-profile, family-based business named Cooley Distillery. Jack was Managing Director of Cooley Distillery, the business his father founded in 1987. At Cooley Distillery, he acquired a wealth of professional experience in whiskey distilling and selling. When the distillery was sold to a large US spirits company in 2012, Jack pursued his own entrepreneurial venture in Irish whiskey. A year after the business was founded, Jack was joined by his brother Stephen Teeling, and together they have shaped their idea for a boutique, premium whiskey distiller producing innovative offerings into a fast growing, internationalized business. Jack and Stephen need to build a niche for TWC, as many new distilleries are due to enter the market.
Originally published in O'Gorman, C., Brophy, M., & Clinton, E. (2015). Teeling Whiskey Company: A tradition of family entrepreneurship and whiskey distilling. The International Journal of Entrepreneurship and Innovation, 16(3), 217225. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Teeling Whiskey Company Ltd; Family-owned business enterprises -- Case studies; Whiskey industry -- Case studies